Set adrift : a mystery and a memoir : my family's disappearance in the Bermuda Triangle - Conover, Sarah (55 Fathoms Publishing LLC, 2023)
"In January, 1958, a renowned sailing family was lost in a storm in the Bermuda Triangle. The youngest of two daughters, Sarah, suddenly an orphan, grew up never knowing her parents and grandparents. As an adult, she began to pursue the mystery of her family and their disappearance, and discovered that their stories were far different from the versions she was told. Sarah Conover's memoir follows the national media's investigation of the Revonoc's vanishing, and exposes the truths that led her to unstory the family history, creating a new understanding of their lives, and hers. Set Adrift weaves Conover's superbly written memoir with interviews, magazine articles, and official Coast Guard reports to chart her fascinating life story. While still infants, she and her sister were the subjects of a custody battle between their grandmother, Mere, and their eventual adoptive parents, Fran and Dick, whose lives, and those of their lost parents and grandparents, were shrouded in myths born of the fight for the girls' affections. Later, Sarah created her own life, and through her personal growth was able to explore the lives of her ancestors, ultimately realizing the truth about both them, and those who remained. Set Adrift begins as a story about loss and loneliness, but blossoms into one of love and belonging."--Publisher marketing.